Evaluation of Collaborative Skills and Their Impact on Elementary School Students' Understanding of Cultural Diversity Concepts - I Desak Nyoman Detri Maharani; I Ketut Gading; Ni Luh Putu Agetania (Universitas Pendidikan Ganesha, 2026)
The problem of low collaboration skills and student learning outcomes in Pancasila Education subjects, due to the dominance of direct learning, forms the background for the urgency of this research. This study aims to analyze the effects of implementing a multimedia-assisted cooperative learning model on students' collaborative skills and understanding of cultural diversity. The research is a quasi-experimental study with a nonequivalent control group design. The research subjects were fifth-grade elementary school students selected through cluster random sampling techniques. Before the treatment, the equality of the initial abilities between the two groups was confirmed using ANOVA. Data collection was carried out using essay test instruments to measure cognitive learning outcomes and observation sheets to measure collaboration skills, and the data were then analyzed using MANOVA. The results showed a significant effect of the learning model on both dependent variables, where the experimental group showed a higher average achievement than the control group. These findings suggest that integrating multimedia visualization into teamwork is effective in building conceptual understanding and fostering positive social interactions. It is concluded that this approach is a strategic solution to optimize the academic and social competence of elementary school students.